Understanding Work Procrastination: Causes, Impacts, and Management Strategies - Sánchez Sarria, Mayerly Zuleima (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Procrastination in the contemporary workplace, a complex phenomenon, has been thoroughly investigated from its causes to its management strategies in a comprehensive research project. Lack of intrinsic motivation and low self-efficacy emerge as key elements in the genesis of work-related procrastination, and their interconnection creates a detrimental cycle. Social expectations and organizational culture play a crucial role, influencing the tendency to postpone tasks. Individually, procrastination is linked to elevated stress levels, decreased job satisfaction, and impaired self-esteem, while at the organizational level, it affects labor efficiency, work quality, and competitiveness. Management strategies, both at the individual and organizational levels, underscore the importance of self-regulation, time management, and the creation of environments that foster self-discipline. This comprehensive analysis underscores the need to simultaneously address psychological, sociocultural, and organizational aspects to effectively manage work-related procrastination, thereby promoting healthier and more productive work environments